The skull of truth - Coville, Bruce; Lippincott, Gary A. (Orlando, Fla. : Magic Carpet Books, 2007)
Charlie, a sixth-grader with a compulsion to tell lies, acquires a mysterious skull that forces its owner to tell only the truth, causing some awkward moments before he understands its power.
"A magic shop book."
Elem. School Library Collection
Wilson's Children
Wilson's Junior High School
5.0
3-6.
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Honesty -- Juvenile fiction; Schools -- Juvenile fiction; Family life -- Fiction; Friendship -- Fiction; Honesty -- Fiction; Schools -- Fiction; Family life -- Fiction; Friendship -- Fiction; Honesty -- Fiction; School stories